Intensive evaporation and boiling of a heterogeneous liquid droplet with an explosive disintegration in high-temperature gas area; Thermal Science; Vol. 20, iss. 2 - Piskunov M. V. Maksim Vladimirovich (2016, 2016)
Title screen